Troubling heroes: Reframing the environmental justice contributions of the Flint water crisis. (28th March 2021) - Carrera, Jennifer S.; Key, Kent
Abstract: While the story of the Flint water crisis has been shared widely, the popular narrative—described in multiple documentaries and as evidenced by accolades heaped upon a limited few number of actors involved with Flint—largely leaves out the broad experiences and actions of Flint residents in responding to the crisis, raising awareness, and advocating for change. Academic literature has contributed to reinforcing an abbreviated and disempowered version of the narrative where Flint residents needed rescue. In this article, we present an extended description of the Flint water crisis leading up to the water switch in April 2014, including descriptions of community mobilization efforts to call government actions into account and produce investigations that validated the concerns of the residents. We offer a review of prominent academic literature demonstrating patterns of erasure that suggest Flint residents were disempowered. In response, we offer three examples which demonstrate how Flint resident mobilizations have broad historical context, national reach, and individual actions that contradict the narrative that Flint residents lack agency and power. In our analysis, rather than viewing Flint residents as in need of rescue by science, we argue that the community mobilization in Flint is indicative of a highly successful implementation of popular epidemiology with profound effects on national conversations about lead in water, drinking water infrastructure management, and environmental justice. This article is categorized under: Human Water > Water Governance Engineering Water Abstract : Flint residents' community mobilization efforts around the Flint Water Crisis viewed within a popular epidemiology frame